PEComa progressed by mTOR inhibitor therapy with anti-VEGFR TKI combined with PD-1 inhibitor: a case report - Wang, Guannan; Sun, Lili; Guan, Jian; Yang, Boyan (Frontiers in Oncology, 2025)
Malignant perivascular epithelioid cell tumors (PEComas) are rare tumors in which the PI3K/AKT/mTOR pathway is critical for pathogenesis and is often associated with mutations in the TSC1/TSC2 genes. First-line mTOR inhibitors are an effective treatment, but metastatic PEComas eventually develop drug resistance and disease progression. A 76-year-old woman presenting with a painful soft tissue mass in the buttocks was diagnosed with malignant PEComa with local invasion and multiple distant metastases, and the tumor cells harbored a TSC2 gene mutation. After disease progression by mTOR inhibitor treatment, immunotherapy combined with anti-angiogenic therapy was enabled, which enabled the patient to achieve a 3-year survival benefit and provided a reference for the treatment of patients with refractory malignant PEComa.